Epilepsy with auditory features: Contribution of known genes in 112 patients. (February 2021) - Bisulli, F.; Rinaldi, C.; Pippucci, T.; Minardi, R.; Baldassari, S.; Zenesini, C.; Mostacci, B.; Fanella, M.; Avoni, P.; Menghi, V.; Caporali, L.; Muccioli, L.; et al.
Highlights: Pathogenic variants in LGI1, RELN, DEPDC5 and SCN1A have been associated with EAF. We aimed to estimate the contribution of these genes in 112 EAF cases. A genetic diagnosis was identified in 9 patients (8%) of our cohort. Our data emphasize the genetic heterogeneity of EAF. Abstract: Epilepsy with Auditory Features (EAF) is a focal epilepsy syndrome mainly of unknown aetiology. LGI1 and RELN have been identified as the main cause of Autosomal Dominant EAF and anecdotally reported in non-familial cases. Pathogenic variants in SCN1A and DEPDC5 have also been described in a few EAF probands belonging to families with heterogeneous phenotypes and incomplete penetrance. We aimed to estimate the contribution of these genes to the disorder by evaluating the largest cohort of EAF. We included 112 unrelated EAF cases (male/female: 52/60) who underwent genetic analysis by next-generation sequencing (NGS) techniques. Thirty-three (29.5%) were familial cases. We identified a genetic diagnosis for 8% of our cohort, including pathogenic/likely pathogenic variants (4/8 novel) in LGI1 (2.7%, CI: 0.6-7.6); RELN (1.8%; CI: 0.2-6.3); SCN1A (2.7%; CI: 0.6-7.6) and DEPDC5 (0.9%; CI 0-4.9).This study shows that the contribution of each of the known genes to the overall disorder is limited and that the genetic background of EAF is still largely unknown. Our data emphasize the genetic heterogeneity of EAF and will inform the diagnosis and management of individuals with this disorder.